Gamasiphis species (Acari: Mesostigmata: Ologamasidae) from Ecuador, with description of a new species and new records - Melo-Molina, Elsa L.; Santos, Jandir C.; de Moraes, Gilberto J.; Castilho, Raphael C. (Zootaxa, 2021)
Gamasiphis Berlese is the most diverse genus of Ologamasidae, with 74 described species, seven of which were described from Ecuador. The main objective of this paper is to report the Gamasiphis species found in surveys recently conducted in Ecuador, including a new species here described, Gamasiphis vikkiae Melo-Molina & Santos n. sp. Complementary descriptions of two previously described species, also collected in this study, are presented.